Foliar cytokinins or brassinosteroids applications influence the rice plant acclimatization to combined heat stress - Pantoja-Benavides, Alvaro Daniel; Garces-Varon, Gabriel; Restrepo-Díaz, Hermann (Frontiers in Plant Science, 2022)
The effect of different foliar sprays numbers of cytokinins – (CK) and brassinosteroids – (BR) on the physiological, biochemical, and panicle parameters of rice plants subjected to combined heat stress (high day/night temperatures) were studied in three different experiments. The treatments established for the first (E1) and second (E2) experiments were the following: i) absolute control, ii) stress control, iii) heat stress + one foliar spray of CK, iv) heat stress + two foliar sprays of CK, v) heat stress + three foliar sprays of CK, vi) heat stress + one foliar spray of BR, vii) heat stress + two foliar sprays of BR, or viii) heat stress + three foliar sprays of BR. For the third experiment (E3), the treatments were the following: i) absolute control, ii) stress control, iii) heat stress + three foliar applications of CK, iv) heat stress + three foliar applications of BR. Rice-stressed plants and sprayed with three foliar sprays of CK or BR had a better stomatal conductance in E1 and E2 compared to their heat-stressed control. The relative tolerance index suggests that three CK or BR applications helped to mitigate the combined heat stress in both experiments. The foliar CK or BR applications at the flowering and grain-filling stages in rice-stressed plants increased Fv/Fm ratio and panicle characteristics (number of filled spikelets and the percentage of panicle blanking in E3). In conclusion, foliar applications of BR or CK can be considered an agronomic strategy to help improve the negative effect of combined heat stress conditions on the physiological behavior of rice plants during different phenological stages.